A produção de roteiro para as histórias em quadrinhos nas plataformas móveis - Barbosa, Nélio da Silva (2017)
This conclusion report of the interdisciplinary professional master's degree in Technologies, Communication and Education of the Universidade Federal de Uberlândia shows the way of construction of a script model for comics on mobile devices. During the work were discussed concepts, characteristics and possible functionalities to be added on comics for mobiles. The proposal also aims to explore the use of the language from other media to complement and to get into the sequential narrative and the idea contributes to the work of screenwriters, designers, researchers and others interested in the digital graphic narrative production for mobile devices.